Impacts of the use of a digital simulation in learning earth sciences (the case of relative dating in high school) - Nafıdı, Youssef; Alamı, Anouar; Zakı, Moncef; El Batrı, Bouchta; Afkar, Hanane (Journal of Turkish Science Education, 2018)
In an attempt to evaluate the impact of the use of a simulation on the learning concepts of relative dating, a study was carried out with first year students at the Technical High School of the city of Taza (Morocco). The method of the study was semi-experimental research design with pre-test and post-test. The study used two groups including the experimental (n = 16) and control (n = 16) groups. The learning outcomes of both groups of students were compared and analysed for significance using the Student’s t-test and the Mann-Whitney U test. The findings showed that the integration of a simulation of relative chronology can have a positive effect on students’ learning if it is properly integrated at an appropriate time during the students’ training.
Keywords: Earth Sciences; relative chronology; high school; learning; simulation